Reconceptualizing Adultery Regulation in Indonesia: A Comparative Analysis of Hudud under Aceh Qanun Jinayat and the National Criminal Code - Danang Dermawan; Mhd Yadi Harahap (ISNU Sumatera Utara, 2026)
The regulation of the crime of adultery in Indonesian law shows that there is a fundamental difference between Qanun Aceh Number 6 of 2014 concerning the Jinayat Law and Law Number 1 of 2023 concerning the Criminal Code. These differences are not only related to the formulation of delicacies, but also reflect the difference in legal paradigm between Islamic criminal law which emphasizes the protection of public morals and national criminal law which is oriented towards the protection of private rights and human rights. This condition raises juridical problems related to consistency, legal certainty, and limits of state authority in regulating the sexual behavior of citizens. This study aims to analyze and compare the conception of adultery, the nature of delicacy, the mechanism of proof, and the orientation of punishment in Qanun Jinayat and the National Criminal Code. This study uses normative legal research methods with legislative, conceptual, and comparative approaches. Legal materials are obtained through literature studies of laws and regulations, Islamic legal sources, and relevant legal literature, then analyzed qualitatively and prescriptively. The results of the discussion show that Qanun Jinayat views adultery as a hudud jarimah with theological and social dimensions, so that it can be processed without complaints and applies very strict evidentiary standards as a form of prudence. The National Criminal Code places adultery as an absolute complaint with a modern evidentiary system, which emphasizes the orientation to the protection of family privacy and honor. This study concludes that the difference in the regulation of adultery reflects the plurality of Indonesian criminal law and demands the harmonization of criminal law policies to be in harmony with religious values, human rights, and the principles of the modern state of law.